2006
DOI: 10.1002/eji.200636426
|View full text |Cite
|
Sign up to set email alerts
|

A distinct subset of intestinal dendritic cells responds selectively to oral TLR7/8 stimulation

Abstract: The intestinal innate immune system continually interacts with commensal bacteria, thus oral vaccines should induce extra/alternative activation of DC, potentially through TLR. To examine this we collected intestinal lymph DC (iL-DC) under steady-state conditions and after feeding resiquimod (R-848), a synthetic TLR7/8 ligand, which we showed induces complete emptying of gut DC into lymph. iL-DC are heterogeneous with subset-specific functions. In this study we determined the kinetics of iL-DC subset release, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 31 publications
8
52
0
Order By: Relevance
“…The mechanism of R848 action is known to be through an indirect activity on plasmacytoid DCs. These cells then secrete high levels of type I IFN, which in turn acts on CD103 + DCs resulting in their activation and migration to the MLN (30,36). We hypothesize that the ability of sFliC to drive CD103 DC migration to the MLN is through the direct ligation of TLR5 on LP CD103 + DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of R848 action is known to be through an indirect activity on plasmacytoid DCs. These cells then secrete high levels of type I IFN, which in turn acts on CD103 + DCs resulting in their activation and migration to the MLN (30,36). We hypothesize that the ability of sFliC to drive CD103 DC migration to the MLN is through the direct ligation of TLR5 on LP CD103 + DCs.…”
Section: Discussionmentioning
confidence: 99%
“…The selective migration of CD103 + DCs to the MLN after sFliC immunization occurred despite Ag being systemically administered. Although atypical for systemic adjuvants, this has been demonstrated after immunization with some subunit oral adjuvants such as R848 and Escherichia coli heat-labile enterotoxin (30,39). Additionally, the B subunit of heat-labile enterotoxin can induce cells with a regulatory phenotype after intranasal administration (40), although it is not clear if these are primed by CD103 + DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of DC migration by CT has been demonstrated by Shreedhar et al (23), who observed that fluorescent microsphereloaded DCs in the subepithelial dome relocated to T cell areas after feeding CT. MacPherson and colleagues have directly addressed the migration of DCs from the intestinal lamina propria by collecting lymph over time in cannulated rats (24 -26). They have shown that DC migration from the lamina propria to the MLN occurs constitutively and that this migration can be modulated by TLR agonists, in particular TLR4 and TLR7/8 agonists (24,25). However, they recently reported that another bacterial toxin with adjuvant activity (heat-labile enterotoxin from Escherichia coli) did not influence DC migration (26).…”
Section: Discussionmentioning
confidence: 99%
“…121 Similarly, the MAP3 (mitogen-activated protein kinase kinase kinase) kinase TPL-2 was also shown to modulate immunity to H. polygyrus, as its deletion in dendritic cells resulted in enhanced resistance to infection that was attributed to its downstream influence on the homing of leukocytes. 122 Indeed, different dendritic cell subsets have divergent expression of certain cytokine and pattern-recognition receptors, [123][124][125][126] and might thus be inherently more or less prone to respond to specific pathogens and cytokines to begin with. These types of signals, in combination with cell-extrinsic cues from epithelial and innate immune cells, could determine which type of dendritic cell that gets activated upon parasite infection.…”
Section: Inductionmentioning
confidence: 99%